REPRESENTASI PEREMPUAN DALAM PEMILIHAN UMUM LEGISLATIF (STUDI KASUS KABUPATEN LEMBATA NUSA TENGGARA TIMUR) - I Putu Yoga Bumi Pradana; Jim Briand Kolianan; Alfred Omri Ena Mau; Hyasintus Alexandro Da Silva (PT. Saha Kreasi Indonesia, 2025)
This research examines the challenges of female representation in legislative elections in Lembata Regency, East Nusa Tenggara, with the aim of understanding the obstacles faced by women in formal political arenas. Despite the implementation of a 30% minimum quota for female representation in the legislature, women in Lembata Regency still face difficulties in achieving elected positions. Using a qualitative case study approach, this study identifies three key dimensions affecting women's representation: macro dimension (political systems and affirmative action policies), meso dimension (the role of political parties), and micro dimension (the individual capacity of female candidates). The findings show that although women meet the administrative quota, structural barriers, patriarchal culture, and unequal political resources still hinder their election. To enhance female representation, more concrete political support and a shift in societal attitudes towards gender inclusivity are needed.